2017
DOI: 10.1002/14651858.cd009196.pub4
|View full text |Cite
|
Sign up to set email alerts
|

EEG for children with complex febrile seizures

Abstract: We attempted to search all possible sources but were unable to find any randomised controlled trials to address the issue up to 23 January 2017. We concluded that there is no high-quality evidence to support or refute the use of an EEG and its timing a er complex febrile seizures in children. Well-designed randomised controlled trials are therefore required. We intend to update this review regularly with the hope that new randomised studies will be reported in the future. EEG for children with complex febrile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 4 , 45 , 90 A 2017 Cochrane systematic review found no randomized controlled trials to refute or support the use of EEG and its timing after complex febrile seizures. 91 …”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“… 4 , 45 , 90 A 2017 Cochrane systematic review found no randomized controlled trials to refute or support the use of EEG and its timing after complex febrile seizures. 91 …”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…In cases in which an EEG is performed, the EEG should be done at least 48 h after the FS to avoid confusing post-ictal electrical activities with abnormal electrical activities [ 14 , 27 , 28 ]. In addition, Harini et al found that EEG slowing was not a significant predictor of epilepsy.…”
Section: Diagnosismentioning
confidence: 99%
“…The child can be discharged after a period of observation in the ED, preferably six hours after the episode. Most FS episodes are short-lived and self-terminating and do not require long-term treatment with antiepileptic drugs [ 27 ]. In a child who is still convulsing at presentation to the ED, indications for giving antiepileptic drugs are seizures lasting more than 5 min, febrile SE, and recurrent seizures.…”
Section: Managementmentioning
confidence: 99%
“…While some studies have demonstrated that an epileptiform EEG was not a sensitive measure and had a poor positive predictive value for the development of epilepsy among neurologically healthy or mildly delayed children with a first complex FS [ 61 , 62 ], others have found that epileptiform discharges on EEGs are predictive risk factors for the development of epilepsy [ 63 , 64 ]. A recent Cochrane review did not find any randomized controlled trials (RCTs) as evidence to support or refute the use of EEG and its timing after complex FS among children [ 65 ].…”
Section: Diagnostic Assessmentsmentioning
confidence: 99%